PENGARUH ASSET GROWTH, LEVERAGE, STRUKTUR AKTIVA DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL - Sherly Milenia; Thio Lie Sha (Jurnal Paradigma Akuntansi, 2023)
This research aims to determine the effect of asset growth, leverage, asset structure and business risk on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. Purposive sampling method was used in determining the sample with several criteria, so that 33 of manufacturing companies were obtained. The data processing technique uses multiple regression analysis using EviewsVersion 12. The results of this study indicate that asset growth and asset structure have a positive and significant effect, while leverage and business risk have a negative and significant effect on capital structure. The implication of this research is to provide benefits as consideration for determining the company's objectives to use the capital structure in improving the company's performance for the better.